Halal Economic Design in the Context of Sustainable Development and Solutions to Environmental Damage - Shochibah Istiqomah; Abdul Mujib; Nikmatul Masruroh (Department of Islamic Economics, Postgraduate Program, UIN Kiai Haji Achmad Siddiq, Indonesia, 2024)
The enactment of the Halal Product Assurance Law No. 33 of 2014 on October 17, 2019, has further brought a breath of fresh air to the development of the halal economy in Indonesia. The halal economy is present as an answer to people's concerns regarding various products circulating in the community, starting from the source, process to successfully becoming a product.